2016
DOI: 10.4172/2169-0286.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Websites of Small-and-Medium-Sized-Hotels (SMHs): A Stages Model of E-Commerce Websites Adoption for Malaysian Hotels

Abstract: This research focuses on examining small-and-medium-sized hotels (SMHs) in Malaysia, specifically their websites, in order to study their e-commerce website stages model. The website evaluation criteria were used to study 193 websites of SMHs to identify the current stage of e-commerce websites adoption in Malaysia. The findings of the study reveal that 69.9 per cent of SMHs websites in Malaysia have online reservation facilities. In terms of social media marketing, this study highlights that 108 out of 193 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Almost half of websites were multilingual in 2010, while this percentage reached 71,4% in 2018, giving the opportunity to more foreign users to visit them and understand their content. The same chance was given to potential clients at 65,3% of websites of small and medium sized hotels in Malaysia (Ayob, 2016). 3,8% of websites in 2010 had a site map, while in 2018 this percentage reached the 30,5%, preventing users to confuse and abandon these websites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost half of websites were multilingual in 2010, while this percentage reached 71,4% in 2018, giving the opportunity to more foreign users to visit them and understand their content. The same chance was given to potential clients at 65,3% of websites of small and medium sized hotels in Malaysia (Ayob, 2016). 3,8% of websites in 2010 had a site map, while in 2018 this percentage reached the 30,5%, preventing users to confuse and abandon these websites.…”
Section: Resultsmentioning
confidence: 99%
“…However, their websites were not characterized by multilingual capabilities, converting them to some extent, into unattractive spots for foreign tourists. On the other hand, results of 193 websites of small and medium sized hotels in Malaysia showed that 65,3% catered to English speakers, while 69,9% provided the opportunity to their users to make online reservations, whereas online cancellation, confirmation and payments were also made available therein, while only 45,0% of websites informed users about privacy and security policy regarding reservations (Ayob, 2016). On the contrary, opposite results were reported by 29 websites of agro-tourism enterprises in Crete, as only a few websites had online reservations, payment system and registration as members.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is important to analyze and understand how the website presence of SMEs such as wine companies is being built. The previous literature in the SMEs’ digital sphere has benefited from developing and using stage models in their business for decades (Rao et al , 2003; Zhu et al , 2009; Ayob, 2016; Burgess, 2016). In the next sections, we present the evolution of these models and our model proposal.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Over the past 10 years, other models have been built, and studies have discussed the application of website stage models in SMEs. Simmons et al (2011) provided an extension from their previous work by using an evaluation model to examine the determinants and outcomes of website features in SMEs. The authors analyzed dimensions focusing on defining a path to the optimization of websites through stages and highlighted the importance of market orientation to a successful implementation of technological innovations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In order to achieve this purpose, appropriate quantitative methods have been underpinned by the perspective of European tourists. Faizal Ayob [13] focuses on examining small-and-medium-sized hotels (SMHs) in Malaysia, specifically their websites, in order to study their ecommerce website stages model. The website evaluation criteria were used to study 193 websites of SMHs to identify the current stage of ecommerce websites adoption in Malaysia.…”
mentioning
confidence: 99%